2015
DOI: 10.1007/s10895-015-1700-4
|View full text |Cite
|
Sign up to set email alerts
|

Symmetric Meso-Chloro-Substituted Pentamethine Cyanine Dyes Containing Benzothiazolyl/Benzoselenazolyl Chromophores Novel Synthetic Approach and Studies on Photophysical Properties upon Interaction with bio-Objects

Abstract: A series of symmetric pentamethine cyanine dyes derived from various N-substituted benzothiazolium/benzoselenazolium salts, and a conjugated bis-aniline derivative containing a chlorine atom at meso-position with respect to the polymethine chain, were synthesized using a novel improved synthetic approach under mild conditions at room temperature. The reaction procedure was held by grinding the starting compounds for relative short times. The novel method is reliable and highly reproducible. Some photophysical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…Cyanine dyes represent a remarkable class of organic compounds, which have found numerous applications in theranostic of tumors [26,27] and fluorescence imaging of biomolecules [28,29] due to their: i) high extinction coefficients; ii) high affinity for biomolecules; iii) longwave absorption and emission bands (near-infrared compounds), enabling highly sensitive in vivo measurements due to the absence of the autofluorescence of the biological molecules in this region, etc. [30,31].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Cyanine dyes represent a remarkable class of organic compounds, which have found numerous applications in theranostic of tumors [26,27] and fluorescence imaging of biomolecules [28,29] due to their: i) high extinction coefficients; ii) high affinity for biomolecules; iii) longwave absorption and emission bands (near-infrared compounds), enabling highly sensitive in vivo measurements due to the absence of the autofluorescence of the biological molecules in this region, etc. [30,31].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…In recent years, structurally diversified low molecular weight derivatives that are able to recognize and delineate tiny structural distinctions of DNA/RNA have attracted increasing interest, due to their various potential applications in many areas [1][2][3][4][5]. Therefore, the design and discovery of new low molecular weight molecules targeting DNA/RNA has been a subject of extensive studies.…”
Section: Introduction Figure 1 Structures Of the Studied Dabco-cyaninmentioning
confidence: 99%
“…Our previous studies revealed that the novel mono-and pentamethine cyanine compounds can be effectively employed as non-covalent labels for nucleic acids [17,19,20]. As a next logical step, herein we directed our efforts towards evaluating the DNA-and RNA-binding ability of the novel trimethine cyanine dye with an emphasis on its use in the drug-displacement studies.…”
mentioning
confidence: 99%